Epidemiological factors associated with abortion. - Pérez, Danny (2015)
Prospective, descriptive, comparative investigation of 252 cases of abortion to determine associated epidemiologic factors and maternal morbidity and mortality at Las Mercedes Regional Teaching Hospital Chiclayo, Peru, from January 1 to June 2, 1993. Seventy eight per cent of all abortions were spontaneous and 21% induced, e. i., 1 abortion per 6 deliveries and an abortion rate of 179,5/1000 live newborns. Maternal mortality due to abortion was 142/1000000 live newborns. We conclude that abortion constitutes a serious public health problem that merits immediate multispecialty and plurisectorial attention.